Electrolyte containing acesulfame sodium additive and secondary battery containing electrolyte
By adding sodium acesulfame additive to the electrolyte of the secondary battery, the problems of high internal resistance, gas generation, poor circulation stability and insufficient thermal stability during the charging and discharging of the battery are solved, and the battery performance and safety are improved.
Patent Information
- Application Number
- CN202411787262.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
AI Technical Summary
During the charging and discharging process, secondary batteries have problems such as high internal resistance, gas generation, poor circulation stability and insufficient thermal stability, which affects their performance and safety.
The electrolyte containing sodium acesulfame additive is used to accurately control the composition of solvents, electrolyte salts and additives, improve the ion conduction performance and electrochemical stability of the electrolyte solution, inhibit the gas production of the battery, and reduce the internal resistance growth rate.
It significantly improves the performance of the electrolyte, reduces the internal resistance of the battery, extends the service life of the battery, and improves the cycle stability and safety of the battery.
Smart Images

Figure BDA0005174375730000161 
Figure BDA0005174375730000171
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to an electrolyte containing an additive and a secondary battery containing the electrolyte. Background Art
[0002] Acesulfame sodium is an organic compound that contains sulfonamide groups and acetyl groups in its molecular structure. This compound has certain stability and solubility in chemical properties and can dissolve and function in a variety of solvents.
[0003] Although secondary batteries, especially lithium-ion batteries and sodium-ion batteries, have made remarkable progress in energy density, cycle life and safety, there are still some issues that need to be addressed.
[0004] The internal resistance of secondary batteries is one of the important factors affecting their performance. High internal resistance will cause the battery to generate a lot of heat during the charging and discharging process, reducing the efficiency and cycle life of the battery. At the same time, high internal resistance will also limit the rate performance of the battery, making it unable to work under high power conditions.
[0005] During the charge and discharge process of the battery, gas may be generated inside the battery due to the side reaction between the electrolyte and the electrode material. These gases will cause the battery volume to expand, increase the internal pressure of the battery, and even cause battery safety problems. Therefore, controlling the battery's gas expansion rate is the key to ensuring battery safety.
[0006] Although the cycle life of secondary batteries has been significantly improved, the structure and performance of electrode materials will still degrade during long-term use. This degradation will lead to a decrease in battery capacity, an increase in internal resistance, and a deterioration in cycle performance. Therefore, improving the cycle stability of batteries is an important way to extend the service life of batteries.
[0007] Under high temperature conditions, the electrochemical performance and safety of secondary batteries may be seriously affected. For example, high temperature may cause problems such as electrolyte decomposition, electrode material structure damage and internal short circuit of the battery. Therefore, improving the thermal stability of the battery is the key to ensure the normal operation of the battery under high temperature conditions. Summary of the invention
[0008] The present invention provides an electrolyte containing sodium acesulfame additive, the electrolyte comprising:
[0009] Solvent components;
[0010] Electrolyte salt components;
[0011] An additive combination comprising 0.2% to 1.0% by mass of acesulfame sodium.
[0012] The mass fraction of the acesulfame sodium is 0.2% to 0.5%.
[0013] The solvent component is prepared by mixing propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a mass ratio of 4:3:3.
[0014] The electrolyte salt component includes sodium hexafluorophosphate (NaPF6) and sodium bis(fluorosulfonyl)imide (NaFSI), and the mass ratio of NaPF6 to NaFSI is 10:2.
[0015] The additives also include 0.5-1.5% by mass of propylene sulfite (PS) and 0.2-0.8% by mass of diethyl sulfate (DTD).
[0016] A method for preparing an electrolyte containing sodium acesulfame additive, the method comprising:
[0017] Propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 4:3:3, and stirred at room temperature until completely mixed;
[0018] Calculate and weigh appropriate amounts of NaPF6 and NaFSI, keeping the mass ratio of NaPF6 to NaFSI at 10:2, slowly add them to the mixed solvent, and stir until completely dissolved;
[0019] Calculate and weigh the required additive combination and slowly add it to the electrolyte, and continue stirring until it is completely uniform;
[0020] Remove excess water from the electrolyte.
[0021] A secondary battery comprising an electrolyte containing sodium acesulfame additive, the battery comprising:
[0022] The positive electrode comprises a sodium nickel iron manganese compound NaNixFeyMnzOX as a positive electrode active material, wherein x, y, z represent the molar ratio of each element, and x+y+z=1, and O is an oxygen element;
[0023] negative electrode;
[0024] An electrolyte solution containing an acesulfame sodium additive;
[0025] The separator is located between the positive and negative electrodes to separate the positive and negative electrodes and allow ions to pass through;
[0026] The battery casing is used to encapsulate the positive electrode, negative electrode, electrolyte and separator to form a complete battery structure;
[0027] The negative electrode is hard carbon
[0028] The electrolyte further comprises one or more of diethyl sulfate (DTD), propylene sulfite (PS), and 1-propylene-1,3-sultone (PST).
[0029] A method for preparing a secondary battery, characterized in that the method comprises:
[0030] Selecting NaNixFeyMnzOX as a positive electrode active material, a hard carbon material as a negative electrode material, and an electrolyte solvent consisting of one or more of propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC);
[0031] dissolving electrolyte salt and electrolyte additive in the electrolyte;
[0032] The positive electrode material and the negative electrode material are coated on the current collector respectively, and then dried and compacted to form the electrode sheet;
[0033] The pole piece, the separator and the electrolyte containing sodium acesulfame are assembled into a battery unit, and the battery unit is sealed to prepare a secondary battery containing sodium acesulfame electrolyte.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0035] The performance of the electrolyte is significantly improved by precisely controlling the composition of solvents, electrolyte salts and additives, especially the addition of sodium acesulfame. As an additive, sodium acesulfame not only improves the ion conductivity and electrochemical stability of the electrolyte, but also effectively inhibits the gas production of the battery during the charge and discharge process, reduces the internal resistance growth rate of the battery, and thus extends the battery life.
[0036] Due to the optimization of the electrolyte, the prepared secondary battery has excellent electrochemical performance. The battery has a high first coulombic efficiency, which means that the energy conversion efficiency is high during the first charge and discharge process, reducing energy loss. At the same time, the battery can maintain a high capacity retention rate during the cycle, and can maintain a high capacity even after a long cycle, showing excellent cycle stability.
[0037] By adding additives such as sodium acesulfame, the gas production of the battery is effectively suppressed, the battery's gas expansion rate is reduced, and the battery's safety is improved. This is of great significance for preventing potential safety hazards such as structural damage and electrolyte leakage caused by increased internal pressure during the battery's charge and discharge process. DETAILED DESCRIPTION
[0038] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0039] The detailed technical scheme for protecting the present invention is as follows:
[0040] Electrolyte preparation:
[0041] In sodium-ion batteries, the electrolyte acts as a medium for ion transmission, and its performance has a crucial impact on the overall performance of the battery. The detailed steps for preparing the electrolyte are as follows:
[0042] Preparation of solvent: Propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 4:3:3. PC has a higher dielectric constant and is conducive to the dissolution of salts; DEC and EMC can reduce the viscosity of the electrolyte and improve the ion mobility.
[0043] Sodium hexafluorophosphate (NaPF6) and sodium bis(trifluoromethane)sulfonyl imide (NaFSI) are added to the above solvent in a ratio of 10:2. These two salts are selected because they can provide high ionic conductivity and have good thermal and chemical stability. In addition to NaPF6 and NaFSI, other sodium salts such as sodium trifluoromethanesulfonate (NaOTf) or sodium bis(trifluoromethane)sulfonyl imide (NaTFSI) can also be considered as electrolyte salts, which also show good electrochemical performance.
[0044] Adjust the salt concentration to between 0.8-1.2 mol / L, especially 1 mol / L. This ensures sufficient ionic conductivity while avoiding excessive viscosity that affects ion migration. The concentration can be adjusted within a certain range, such as 0.8 mol / L to 1.2 mol / L, to optimize battery performance.
[0045] Add a combination of additives that accounts for 1-3% of the total mass of the electrolyte. The additive is 0.2-1% sodium acesulfame. The selection of additives is intended to further enhance the electrochemical properties of the electrolyte, such as reducing battery polarization, inhibiting dendrite growth, etc. Commonly used additives include DTD (vinyl sulfate), PS (propylene sulfite), PST (1-propylene-1,3-sulfonate), etc., which can be used as film-forming additives, antioxidants or flame retardants. In addition, new additives such as NaODFB (sodium difluorooxalatoborate) and TVS (tetravinylsilane) also show good application prospects and can be used to improve the cycle stability and safety of batteries.
[0046] The electrolyte preparation process needs to ensure that all components are fully mixed to avoid inconsistent performance due to concentration gradients. Water content will seriously affect the performance and safety of the battery, so the moisture content should be strictly controlled during the preparation process. For purchased raw materials, they should be purified to remove impurities and moisture.
[0047] Preparation of sodium ion batteries:
[0048] The preparation process of sodium-ion batteries involves multiple key steps, including material selection, electrode preparation, electrolyte formulation, battery assembly and testing, etc. Each step has an important impact on the final performance of the battery.
[0049] 1. Material selection
[0050] The cathode material is one of the most critical materials in sodium-ion batteries, and its performance directly affects the energy density, cycle stability and rate performance of the battery. At present, the commonly used sodium-ion cathode materials include layered oxides, Prussian blue compounds, polyanionic compounds and organic cathode materials.
[0051] Layered oxides: Layered oxide cathode materials, such as NaNixFeyMnzOX, have high specific capacity, good cycle stability and rate performance. The battery performance can be further optimized by adjusting the ratio of Ni, Fe, and Mn. The structure of this type of material is similar to the layered oxide cathode material in lithium-ion batteries, but has a higher sodium ion capacity.
[0052] Prussian blue compounds: Prussian blue compounds have an open three-dimensional framework structure, which is conducive to the rapid diffusion of sodium ions. This type of material usually has a high specific capacity and good cycle stability, but its preparation process is relatively complex and the cost is high.
[0053] Polyanionic compounds: Polyanionic compounds, such as sodium phosphate, sodium pyrophosphate, etc., have stable structures and high safety. Such materials usually have high thermal and chemical stability, but relatively low specific capacity.
[0054] Organic cathode material: Organic cathode material is a new type of cathode material with the advantages of abundant resources, environmental friendliness and recyclability. However, the conductivity and stability of this type of material are relatively poor, and further modification and optimization are needed.
[0055] Anode materials are another key component in sodium-ion batteries, and their performance also affects the battery's energy density, cycle stability, and rate performance. Currently, commonly used sodium-ion anode materials include hard carbon, graphite, alloy materials, metal oxides, and organic anode materials.
[0056] Hard carbon: Hard carbon is a carbon material with a disordered structure and a large interlayer spacing, which is conducive to the insertion and deintercalation of sodium ions. As the negative electrode material of sodium ion batteries, hard carbon shows good cycle stability and high specific capacity. However, the first coulombic efficiency of hard carbon is low and the cost is relatively high.
[0057] Graphite: Graphite is a commonly used negative electrode material, but the original graphite has a poor capacity for sodium ions. Through modification, such as expanding the interlayer spacing, introducing defects or doping with other elements, the capacity of graphite for sodium ions can be increased, thereby improving its electrochemical performance.
[0058] Alloy materials: Alloy materials, such as tin-based alloys and antimony-based alloys, have high specific capacity and good conductivity. However, these materials are prone to volume expansion and contraction during the charge and discharge process, resulting in the destruction of the electrode structure and the decrease of cycle stability.
[0059] Metal oxides: Metal oxides, such as iron oxide and molybdenum oxide, can also be used as negative electrode materials for sodium ion batteries. These materials usually have higher specific capacity and better cycle stability, but poor conductivity and need to be used in combination with other conductive materials.
[0060] Organic anode materials: Similar to organic cathode materials, organic anode materials also have the advantages of abundant resources, environmental friendliness and recyclability. However, the stability and conductivity of such materials also need further modification and optimization.
[0061] Electrolyte is an important component of sodium-ion batteries, and its performance directly affects the battery's ion conduction, cycle stability and safety. Currently, commonly used sodium-ion battery electrolytes mainly include organic solvent-based electrolytes and solid electrolytes.
[0062] Organic solvent-based electrolyte: Organic solvent-based electrolyte is usually composed of sodium salt (such as sodium hexafluorophosphate, sodium perchlorate, etc.) and organic solvent (such as ethylene carbonate, dimethyl carbonate, etc.). This type of electrolyte has high ion conductivity and good chemical stability, but it is flammable and explosive, and there are certain safety risks.
[0063] The separator is one of the key components in sodium-ion batteries. Its main function is to isolate the positive and negative electrodes, prevent short circuits, and allow ions to pass through. Currently, commonly used separator materials include polypropylene (PP), polyethylene (PE), or their composite films.
[0064] Polypropylene (PP) and polyethylene (PE): PP and PE are commonly used separator materials with good mechanical strength, chemical stability and ion permeability. However, these materials have relatively poor thermal stability and are prone to shrinkage and melting at high temperatures, leading to battery short circuits and safety hazards.
[0065] Composite membrane: In order to improve the performance and safety of the diaphragm, a composite membrane can be used as a diaphragm material. Composite membranes are usually composed of multiple materials, such as composite membranes of PP and PE, inorganic ceramic coating composite membranes, etc. These composite membranes have better mechanical strength, thermal stability and ion permeability, which can improve the safety and performance of the battery.
[0066] 2. Electrode Preparation
[0067] Electrode preparation is one of the key steps in the preparation of sodium-ion batteries. The electrode preparation process includes material mixing, coating, drying and tableting.
[0068] The positive or negative electrode materials, conductive agents and binders are mixed evenly in a certain proportion to form an electrode slurry. The conductive agent can improve the conductivity of the electrode, while the binder can firmly bond the electrode material to the current collector. The electrode slurry is evenly coated on the current collector to form an electrode sheet. The coating thickness and uniformity need to be controlled during the coating process to ensure the performance and consistency of the electrode. The coated electrode sheet is dried to remove the solvent and moisture. The drying temperature and time need to be set according to the properties of the electrode material to avoid damage to the electrode material and performance degradation. The dried electrode sheet is pressed to increase the density and mechanical strength of the electrode. The pressure and temperature need to be controlled during the pressing process to ensure the flatness and consistency of the electrode.
[0069] 3. Electrolyte preparation
[0070] Electrolyte preparation is another key step in the preparation of sodium-ion batteries. The electrolyte preparation process includes steps such as dissolution, mixing and filtration.
[0071] Sodium salt and organic solvent are mixed in a certain proportion and heated to a certain temperature to completely dissolve the sodium salt in the organic solvent. The dissolved electrolyte is mixed evenly to ensure the consistency of the composition and performance of the electrolyte. The mixed electrolyte is filtered to remove impurities and particles to ensure the purity and stability of the electrolyte.
[0072] 4. Battery Assembly
[0073] Battery assembly is the last step in the preparation of sodium-ion batteries. The assembly process includes electrode stacking, separator placement, electrolyte injection, and sealing.
[0074] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence to form the core part of the battery. During the stacking process, it is necessary to ensure the alignment and close contact between the components to avoid internal short circuit or electrolyte leakage. A separator is placed between the positive and negative electrodes to isolate the positive and negative electrodes and prevent short circuit. The separator needs to have good ion permeability and mechanical strength to ensure the performance and safety of the battery. Inject the prepared electrolyte into the battery to fully infiltrate the electrodes and separator. The amount and injection method of the electrolyte need to be set according to the size and performance requirements of the battery to ensure the electrochemical performance and safety of the battery. The battery injected with electrolyte is sealed to prevent electrolyte leakage and external impurities from entering the battery. The sealing method can be mechanical sealing, laser welding, etc. to ensure the sealing and stability of the battery.
[0075] Battery assembly and testing
[0076] 1. Battery assembly
[0077] Battery assembly is the last step in the preparation of sodium-ion batteries and a key step in ensuring battery performance and safety. The assembly process requires strict control of the quality and process parameters of each component to ensure the consistency and reliability of the battery.
[0078] Electrode stacking: The positive electrode sheet, separator and negative electrode sheet are stacked in order to form the core part of the battery. During the stacking process, it is necessary to ensure the alignment and close contact between the components to avoid internal short circuits or electrolyte leakage. At the same time, the number and thickness of the electrode sheets need to be controlled to ensure the capacity and performance of the battery.
[0079] Diaphragm placement: A diaphragm is placed between the positive and negative electrodes to isolate the positive and negative electrodes and prevent short circuits. The diaphragm needs to have good ion permeability and mechanical strength to ensure battery performance and safety. When placing the diaphragm, the flatness and position accuracy of the diaphragm need to be ensured.
[0080] Electrolyte injection: Inject the prepared electrolyte into the battery to fully soak the electrodes and diaphragm. The amount of electrolyte and the injection method need to be set according to the size and performance requirements of the battery to ensure the electrochemical performance and safety of the battery. When injecting the electrolyte, the injection speed and pressure need to be controlled to avoid electrolyte leakage or electrode material shedding.
[0081] Sealing treatment: The battery injected with electrolyte is sealed to prevent leakage of electrolyte and foreign impurities from entering the battery. Sealing methods can be mechanical sealing, laser welding, etc. to ensure the sealing and stability of the battery. During the sealing process, the quality and sealing performance of the seal must be ensured to avoid leakage or failure of the battery during use.
[0082] 2. Battery test
[0083] Battery testing is an important part of evaluating the performance and safety of sodium-ion batteries. The testing process needs to simulate actual usage conditions and conduct charge and discharge cycle tests, performance tests, and safety tests on the battery.
[0084] Charge and discharge cycle test: Place the prepared sodium ion battery in a constant temperature box and perform charge and discharge cycle test within a specified voltage range. Test conditions should be set according to actual needs, including temperature, voltage range, charge and discharge current, etc. The test can evaluate the performance indicators of the battery, such as capacity retention rate, impedance growth rate, gas expansion rate, etc. These indicators can reflect the battery's performance in terms of cycle stability, rate performance and safety.
[0085] Performance test: In addition to the charge and discharge cycle test, other performance tests are also required for the battery, such as energy density test, power density test, self-discharge test, etc. These tests can further evaluate the performance characteristics and application scope of the battery. For example, the energy density test can evaluate the energy storage capacity of the battery; the power density test can evaluate the charge and discharge rate of the battery; and the self-discharge test can evaluate the power loss of the battery during storage.
[0086] Safety testing: Safety testing is an important part of evaluating the safety of sodium-ion batteries. The tests include overcharge testing, over-discharge testing, short-circuit testing, and puncture testing. These tests can simulate the potential safety hazards that the battery may encounter during use and evaluate the safety performance and countermeasures of the battery. For example, the overcharge test can evaluate the safety performance of the battery under overcharge; the short-circuit test can evaluate the protection mechanism of the battery under short-circuit conditions; and the puncture test can evaluate the safety performance of the battery when subjected to external impact.
[0087] Electrolyte Preparation Example 1:
[0088] Weigh appropriate amounts of propylene carbonate, diethyl carbonate and ethyl methyl carbonate according to the mass ratio of PC:DEC:EMC=4:3:3. Place the weighed solvent in a clean container and stir with a magnetic stirrer at room temperature until it is completely mixed.
[0089] According to the required total amount of electrolyte and the concentration of electrolyte salt (1 mol / L), calculate and weigh the appropriate amount of NaPF6 and NaFSI, keeping the ratio of NaPF6:NaFSI = 10:2. Slowly add the weighed electrolyte salt to the mixed solvent, stirring while adding to ensure that the salt is completely dissolved and no solid residue remains.
[0090] Calculate and weigh the required additive combination, i.e. 1.5% PS, 0.5% DTD and 0.2% sodium acesulfame, based on 2% of the total mass of the electrolyte. Slowly add the additives to the electrolyte and continue stirring until completely homogeneous.
[0091] Use a moisture meter to detect the moisture content in the electrolyte. If necessary, use molecular sieves, vacuum drying or nitrogen purging to remove moisture. Under nitrogen protection, place the electrolyte in a vacuum drying oven and dry it at 60°C for a period of time to remove oxygen in the electrolyte.
[0092] Store the purified electrolyte in a dry, cool, well-ventilated place, away from direct sunlight and high temperature. According to actual needs, the electrolyte can be divided into suitable containers and sealed for storage.
[0093] Example 2
[0094] Similar to Example 1, this example also uses PC, DEC, and EMC as solvents, and NaPF6 and NaFSI as electrolyte salts. The difference is that in the additive combination, the proportion of sodium acesulfame is increased to 0.5% to further study its effect on the performance of the electrolyte.
[0095] Example 3
[0096] In this example, 0.5% sodium difluorooxalatoborate (NaODFB) is added as an additive to the electrolyte containing 1.5% PS and 0.5% DTD to study its effect on the performance of the electrolyte. Other steps are similar to those in Example 1.
[0097] Example 4
[0098] In this example, 0.5% tetravinylsilane (TVS) is added as an additive to an electrolyte containing 1.5% PS and 0.5% DTD to explore its effect on the performance of the electrolyte. Other steps are similar to those in Example 1.
[0099] Comparative Example 1
[0100] Electrolyte composition: solvent is propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) (mass ratio 4:3:3); electrolyte salt is sodium hexafluorophosphate (NaPF6) and sodium bis(fluorosulfonyl)imide (NaFSI) (total concentration 1 mol / L, ratio NaPF6:NaFSI=10:2); additive is 1.5% propylene sulfite (PS) + 0.5% ethylene sulfate (DTD).
[0101] The electrolyte was prepared according to the experimental steps in Example 1, including solvent preparation, electrolyte salt dissolution, additive addition, electrolyte purification treatment, and storage and packaging.
[0102] Comparative Example 2
[0103] Electrolyte composition: solvent is propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) (mass ratio 4:3:3); electrolyte salt is sodium hexafluorophosphate (NaPF6) and sodium bis(fluorosulfonyl)imide (NaFSI) (total concentration 1 mol / L, ratio NaPF6:NaFSI=10:2); additive is 1.5% propylene sulfite (PS) + 0.5% ethylene sulfate (DTD) + 0.5% 1-propylene-1,3-sultone (PST)
[0104] The electrolyte was prepared according to the experimental steps in Example 1.
[0105] Sodium ion battery preparation
[0106] 1. Material selection and preparation.
[0107] The positive electrode material is selected as sodium nickel iron manganese compound NaNi x Fe y Mn z O X As the positive electrode active material, x, y, and z represent the molar ratio of each element, and O is the oxygen element, which ensures that the material has high energy density and good cycle stability.
[0108] The negative electrode material is made of hard carbon material, which is an ideal negative electrode material for sodium ion batteries because of its stable structure and high sodium storage capacity.
[0109] Electrolyte solvent: Propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 4:3:3 to obtain a uniform electrolyte solvent.
[0110] Electrolyte salt: Sodium hexafluorophosphate (NaPF6) and sodium bis(fluorosulfonyl)imide (NaFSI) were selected as electrolyte salts and mixed in a ratio of NaPF6:NaFSI=10:2 with a total concentration of 1 mol / L to ensure that the electrolyte has good ion conductivity and electrochemical stability.
[0111] Additives: According to the requirements of the examples and comparative examples, additives in different combinations and proportions were prepared, including DTD (vinyl sulfate), PS (propylene sulfite), PST (1-propylene-1,3-sultone), sodium acesulfame, NaODFB (sodium difluorooxalatoborate) and TVS (tetravinylsilane).
[0112] 2. Electrolyte preparation
[0113] Add electrolyte salt to the solvent and stir thoroughly until completely dissolved; according to the set additive combination and ratio, accurately weigh the additives and add them to the electrolyte, and stir again to fully evenly; purify the electrolyte to remove impurities and moisture to ensure the quality of the electrolyte; store the treated electrolyte in a special container and prepare it for battery assembly.
[0114] 3. Battery Assembly
[0115] The positive electrode material and the negative electrode material are coated on the current collector respectively, and the pole pieces are made through drying, compaction and other steps; the pole pieces are assembled into battery cells together with the separator and the electrolyte to ensure that no impurities and moisture enter during the assembly process; the battery cells are sealed to make sodium ion batteries.
[0116] 4. Battery testing and evaluation
[0117] The prepared sodium ion battery was placed in a 45°C constant temperature box for charge and discharge cycle tests. The test conditions were as follows: 1C constant current and constant voltage charging and 1C constant current and discharge cycle tests were performed in the voltage range of 2.62-4.25V, the constant current and constant voltage charging cutoff current was 0.05C, and each step of charging and discharging was left alone for 2 minutes. The discharge capacity, impedance and volume of the battery before the cycle, as well as the discharge capacity, impedance and volume after 1000 cycles were recorded. Based on the recorded data, the battery's first coulombic efficiency, capacity retention rate, impedance growth rate and gas expansion rate and other performance indicators were calculated and evaluated.
[0118] Test Method
[0119] Test environment and methods. The temperature of the thermostat is set at 45°C, which is a relatively high temperature designed to simulate the working conditions of the battery in a high temperature environment. High temperature will accelerate the chemical reaction inside the battery, thereby exposing the battery's performance defects more quickly.
[0120] The charge and discharge voltage range is set at 2.62-4.25 V. This voltage range is determined based on the characteristics of sodium-ion batteries and is designed to ensure that the battery operates within a safe voltage range while being able to fully demonstrate its performance.
[0121] The test was conducted using 1C constant current and constant voltage charging and 1C constant current and discharge cycles. 1C means that the battery's charge and discharge current is 1 times its rated capacity, i.e. if the battery capacity is 1000mAh, the 1C current is 1000mA. The constant current and constant voltage charging mode means that the battery is charged at a constant current at the beginning of the charge. When the voltage reaches the set value, it is switched to constant voltage charging until the charging current drops to the set cutoff current (0.05C). The constant current discharge mode is a discharge with a constant current until the voltage drops to the set discharge cutoff voltage.
[0122] Each step of charging and discharging is followed by a 2-minute rest period to simulate the short rest or standby state that the battery may experience in actual use. It also helps the ion and charge distribution inside the battery to reach a relatively stable state, thereby more accurately evaluating the battery's performance.
[0123] Test indicators and calculation methods
[0124] The capacity retention rate refers to the ratio of the discharge capacity of a battery to its initial discharge capacity after a certain number of charge and discharge cycles. Calculation formula: Capacity retention rate = discharge capacity after cycle / discharge capacity before cycle × 100%.
[0125] Capacity retention is an important indicator to measure the cycle stability of batteries. A high capacity retention means that the battery can still maintain a high capacity after multiple charge and discharge cycles, thus having a longer service life.
[0126] The impedance growth rate refers to the percentage increase in the ratio of the impedance of the battery to the initial impedance after a certain number of charge and discharge cycles. The calculation formula is: Impedance growth rate = (impedance after cycle - impedance before cycle) / impedance before cycle × 100%.
[0127] Impedance is a measure of the internal resistance of a battery, which directly affects the battery's charge and discharge efficiency and performance. The impedance growth rate reflects the change in the battery's internal resistance during the cycle. A low impedance growth rate means that the battery's internal resistance increases less during the cycle, resulting in better electrochemical performance and a longer service life.
[0128] The expansion rate refers to the percentage increase in the volume of a battery compared to its initial volume after a certain number of charge and discharge cycles. Calculation formula: expansion rate = (volume of battery after cycle - initial battery volume) / initial battery volume × 100%.
[0129] The gas expansion rate is an indicator to measure the volume expansion degree of the battery during the cycle. A high gas expansion rate may lead to increased internal pressure of the battery, structural damage, electrolyte leakage and other problems, seriously affecting the safety and service life of the battery. Therefore, controlling the gas expansion rate is an important consideration in the battery design and manufacturing process.
[0130] The electrolyte of Example 1 is used in sodium ion batteries
[0131] First coulombic efficiency: 85.1%, indicating that the battery has a high energy conversion efficiency during the first charge and discharge process.
[0132] Initial internal resistance percentage: 95%. Compared with other embodiments and comparative examples, the initial internal resistance is lower, which is beneficial to the charge and discharge performance of the battery.
[0133] Cycle 1000 cycles performance:
[0134] 1. Capacity retention rate: 92.6%, indicating that the battery can still maintain a high capacity after a long period of cycling and has good cycle stability.
[0135] 2. Gas expansion rate: 53.2%, which is significantly lower than that of the comparative example and other embodiments, indicating that sodium acesulfame is effective in inhibiting gas production in batteries.
[0136] 3. Internal resistance growth rate: 14.2%, the internal resistance growth is slow, which is conducive to the long life of the battery.
[0137] The electrolyte of Example 2 is used in sodium ion batteries
[0138] The first coulombic efficiency was 85.8%, which was slightly higher than that in Example 1, indicating that increasing the proportion of sodium acesulfame was helpful in improving the first coulombic efficiency.
[0139] Initial internal resistance percentage: 80%, the initial internal resistance is further reduced, which is beneficial to improving the charging and discharging performance of the battery.
[0140] Cycle 1000 cycles performance:
[0141] 1. Capacity retention rate: 93.5%, the highest among all embodiments and comparative examples, indicating that the battery has excellent cycle stability.
[0142] 2. Gas expansion rate: 5.6%, the lowest among all the embodiments and comparative examples, further verifying the significant effect of sodium acesulfame in inhibiting battery gas production.
[0143] 3. Internal resistance growth rate: 13.6%, the internal resistance grows slowly, which is conducive to the long life of the battery.
[0144] The electrolyte of Example 3 is used in sodium ion batteries
[0145] The first coulombic efficiency was 86.1%, the highest among all the embodiments and comparative examples, indicating that the addition of NaODFB was helpful to improve the first coulombic efficiency.
[0146] Initial internal resistance percentage: 105%, the initial internal resistance is relatively high, but still within an acceptable range.
[0147] Cycle 1000 cycles performance:
[0148] 1. Capacity retention rate: 90.6%, slightly lower than that of Example 1 and Example 2, but still has high cycle stability.
[0149] 2. Gas expansion rate: 65.4%, higher than Example 1 and Example 2, but lower than Comparative Example 1 and Comparative Example 2, indicating that NaODFB has a certain effect in inhibiting battery gas production, but not as significant as sodium acesulfame.
[0150] 3. Internal resistance growth rate: 14.9%, similar to Example 1, the internal resistance growth is slower.
[0151] The electrolyte of Example 4 is used in sodium ion batteries
[0152] The first coulombic efficiency is 84.6%, which is slightly lower than that of other embodiments, but still has a high energy conversion efficiency.
[0153] Initial internal resistance percentage: 120%, the initial internal resistance is relatively high, which may affect the charge and discharge performance of the battery.
[0154] Cycle 1000 cycles performance:
[0155] 1. Capacity retention rate: 85.4%, which is lower than other embodiments, but still has a certain cycle stability.
[0156] 2. Gas expansion rate: 67.7%, which is higher than other embodiments, but lower than Comparative Examples 1 and 2, indicating that TVS has a certain effect in inhibiting battery gas production, but not as significant as sodium acesulfame and NaODFB.
[0157] 3. Internal resistance growth rate: 29.5%, the highest among all embodiments and comparative examples. The internal resistance grows fast, which may affect the long life operation of the battery.
[0158] The electrolyte of Comparative Example 1 is used for sodium ion battery
[0159] First coulombic efficiency: 80.5%, which is lower than all the examples, indicating that the lack of synergistic effect of other additives will affect the first coulombic efficiency.
[0160] Initial internal resistance percentage: 100%, as a benchmark comparison, the initial internal resistance is at a medium level.
[0161] Cycle 1000 cycles performance:
[0162] 1. Capacity retention: 79.4%, which is lower than all the examples, indicating that the lack of synergistic effect of other additives will affect the cycle stability of the battery.
[0163] 2. Gas expansion rate: 95.4%, the highest among all the examples and comparative examples, indicating the lack of effective gas generation inhibitor.
[0164] 3. Internal resistance growth rate: 14.9%, which is similar to that of Example 1 and Example 3, but the overall performance is poor due to poor other properties.
[0165] The electrolyte of Comparative Example 2 is used for sodium ion battery
[0166] The first coulombic efficiency is 85.2%, which is slightly higher than that of comparative example 1, but still lower than that of all the embodiments, indicating that the addition of PST has limited effect on the improvement of the first coulombic efficiency.
[0167] Initial internal resistance percentage: 110%, the initial internal resistance is relatively high, which may affect the charge and discharge performance of the battery.
[0168] Cycle 1000 cycles performance:
[0169] 1. Capacity retention rate: 92.7%, slightly higher than that of Comparative Example 1, but still lower than that of all the examples, indicating that the addition of PST has limited effect on the improvement of the cycle stability.
[0170] 2. Gas expansion rate: 89.5%, higher than all the examples, but lower than Comparative Example 1, indicating that PST has a certain effect in inhibiting battery gas production, but not as significant as sodium acesulfame.
[0171] 3. Internal resistance growth rate: 15.5%, which is higher than all the examples. The internal resistance grows faster, which may affect the long-life operation of the battery.
[0172]
[0173]
[0174] By comparing the sodium ion battery performance evaluation results of Examples 1-4 and Comparative Examples 1-2, the following conclusions can be drawn:
[0175] Addition of sodium acesulfame: In Examples 1 and 2, the addition of sodium acesulfame significantly reduced the initial internal resistance and gas expansion rate of the battery and improved the cycle stability of the battery. In particular, in Example 2, the increase in the proportion of sodium acesulfame further improved the performance of the battery. This shows that sodium acesulfame plays an important role in improving the performance of sodium ion batteries.
[0176] Effects of different additives: By comparing Example 3 and Example 4, we can see the effects of NaODFB and TVS as additives on battery performance. Although NaODFB improves the initial coulombic efficiency, the gas expansion rate and internal resistance growth rate are relatively high; while TVS has a certain effect in inhibiting battery gas production, but the initial internal resistance is high, and the capacity retention rate and internal resistance growth rate are not as good as those of other examples. This shows that different additives have different effects on battery performance.
[0177] Performance of the comparative examples: In comparative examples 1 and 2, the battery performance is relatively poor due to the lack of an effective combination of additives. In particular, the gas expansion rate and internal resistance growth rate are high, which seriously affects the cycle stability and long-life operation of the battery. This shows that the selection and combination of additives have an important influence on the performance of sodium-ion batteries.
[0178] In summary, the performance of sodium-ion batteries can be significantly improved by optimizing the combination and ratio of additives. In particular, the addition of sodium acesulfame has shown significant effects in reducing initial internal resistance, inhibiting battery gas production, and improving cycle stability.
[0179] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte containing sodium acesulfame additive, characterized in that: The electrolyte comprises: a solvent component; Electrolyte salt components; An additive combination comprising 0.2% to 1.0% by mass of acesulfame sodium.
2. The electrolyte containing sodium acesulfame additive according to claim 1, characterized in that: The mass fraction of the acesulfame sodium is 0.2% to 0.5%.
3. The electrolyte containing sodium acesulfame additive according to claim 1, characterized in that: The solvent component is prepared by mixing propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a mass ratio of 4:3:
3.
4. The electrolyte containing sodium acesulfame additive according to claim 1, characterized in that: The electrolyte salt component includes sodium hexafluorophosphate (NaPF6) and sodium bis(fluorosulfonyl)imide (NaFSI), and the mass ratio of NaPF6 to NaFSI is 10:
2.
5. The electrolyte containing sodium acesulfame additive according to claim 1, characterized in that: The additives also include 0.5-1.5% by mass of propylene sulfite (PS) and 0.2-0.8% by mass of diethyl sulfate (DTD).
6. A method for preparing an electrolyte containing sodium acesulfame additive according to any one of claims 1 to 5, characterized in that: The method includes: Propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 4:3:3, and stirred at room temperature until completely mixed; Calculate and weigh appropriate amounts of NaPF6 and NaFSI, keeping the mass ratio of NaPF6 to NaFSI at 10:2, slowly add them to the mixed solvent, and stir until completely dissolved; Calculate and weigh the required additive combination and slowly add it to the electrolyte, and continue stirring until it is completely uniform; Remove excess water from the electrolyte.
7. A secondary battery comprising the electrolyte containing sodium acesulfame additive according to claims 1-5, characterized in that: The battery includes: The positive electrode comprises a sodium nickel iron manganese compound NaNixFeyMnzOX as a positive electrode active material, wherein x, y, z represent the molar ratio of each element, and x+y+z=1, and O is an oxygen element; negative electrode; An electrolyte solution containing an acesulfame sodium additive; The separator is located between the positive and negative electrodes to separate the positive and negative electrodes and allow ions to pass through; The battery casing is used to encapsulate the positive electrode, negative electrode, electrolyte and separator to form a complete battery structure.
8. The secondary battery according to claim 7, characterized in that: The negative electrode is hard carbon.
9. The secondary battery according to claim 7, characterized in that: The electrolyte further comprises one or more of diethyl sulfate (DTD), propylene sulfite (PS), and 1-propylene-1,3-sultone (PST).
10. A method for preparing a secondary battery according to claim 7-9, characterized in that: The method comprises: selecting NaNixFeyMnzOX as a positive electrode active material, a hard carbon material as a negative electrode material, and an electrolyte solvent consisting of one or more of propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC); dissolving electrolyte salt and electrolyte additive in the electrolyte; The positive electrode material and the negative electrode material are coated on the current collector respectively, and then dried and compacted to form the electrode sheet; The pole piece, the separator and the electrolyte containing sodium acesulfame are assembled into a battery unit, and the battery unit is sealed to prepare a secondary battery containing sodium acesulfame electrolyte.
